ENTERPRISE MARKETING (ON THE EXAMPLE OF UZBEKISTAN) (American Journal of Business Management, Economics and Banking, 2022)
The first manifestations of marketing activity are attributed to the very beginning of the formation and development of commodity-money relations. Information about the first advertisement of the product is found in the countries of ancient civilization in Sumer, Egypt, in the states of ancient Mesopotamia, Japan [11]. The theoretical foundations of marketing as an independent science existing at the intersection of economics, sociology and management were laid in the XIX century by the American Sares McCormick (1809-1884).